El síndrome de la mujer maltratada en situaciones de conflicto intrafamiliar en el D.M de Quito, durante el año 2022. - Cadena Quiranza Marco Antonio (2025)
The study comprehensively addresses violence against women in various contexts, ranging from intimate relationships to forced displacement and family conflicts, highlighting the unjustifiability of such violence in supposedly loving and respectful environments. Multiple forms of violence are identified, including physical, sexual, and psychological abuse, with their emotional and physical consequences, such as the battered woman syndrome. Its main objective is to propose concrete strategies to address this deeply rooted issue by understanding the cycles of violence in various contexts, drawing on international human rights law and Ecuadorian legislation. This multidisciplinary approach not only identifies manifestations of violence but also systemic and structural obstacles that perpetuate it, seeking to formulate effective measures to protect and empower women. The research is based on the dogmatic legal methodology, which analyzes regulations, jurisprudence, and doctrine to understand the nature and scope of violence against women. This methodology contributes to the study by providing a rigorous analysis of international and local laws, identifying legal gaps and areas for improvement in the protection of women's rights. Additionally, it allows for the contextualization of violence against women within a broader legal framework, facilitating the understanding of its causes and the identification of solutions from a legal perspective. Based on solid legal foundations, the research can offer specific recommendations to address this issue, promoting the protection of women's rights and their empowerment. This comprehensive approach, combining socio-economic, cultural, and legal understanding, is essential for developing effective strategies in the eradication of violence against women. Keywords: Conflict, displacement, human rights, woman, victim, violence.